1981
DOI: 10.1353/aad.2012.1081
|View full text |Cite
|
Sign up to set email alerts
|

Recall of Different Segments of an Interpreted Lecture by Deaf Students

Abstract: In Experiment 1, 20 deaf college students received an interpreted, videotaped presentation of one lecture and a printed presentation of a second lecture. In Experiment 2, 16 deaf students received one interpreted presentation and, then, a second interpreted presentation on a different topic. In both experiments students wrote down the information they remembered immediately after each presentation. Recall protocols were scored for the distribution of ideas recalled from each quarter of the lecture. The princip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…It is noteworthy that scores across the three delivery modes were relatively low, ranging from 30% to 45%. Although no hearing comparison group was included, the comprehension scores observed here are consistent with previous results concerning deaf students' classroom learning with interpreting and real-time text (e.g., Jacobs, 1977;Livingston et al, 1994;Marschark, Sapere, et al, 2004;Murphy & Fleischer, 1979;Stinson et al, 1981).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…It is noteworthy that scores across the three delivery modes were relatively low, ranging from 30% to 45%. Although no hearing comparison group was included, the comprehension scores observed here are consistent with previous results concerning deaf students' classroom learning with interpreting and real-time text (e.g., Jacobs, 1977;Livingston et al, 1994;Marschark, Sapere, et al, 2004;Murphy & Fleischer, 1979;Stinson et al, 1981).…”
Section: Resultssupporting
confidence: 89%
“…The operator produces text as it is spoken by the teacher using a stenographic machine (CART), automatic speech recognition (C-Print), or a standard keyboard (Preminger & Levitt, 1997;Stinson et al, 1999;Viable Technologies Inc., 2002). Stinson, Meath-Lang, and MacLeod (1981) were perhaps the first to examine the utility of print relative to sign language interpreting in the classroom. They found that deaf college students recalled more information when the material was presented in print rather than interpreted, although performance was quite low, ranging from 12% to 56% in various conditions.…”
Section: Text-based Alternatives To Interpretingmentioning
confidence: 99%
“…Five studies have compared support provided by various types of text information to support provided by interpreting. Three studies that compared deaf/hh students' retention of interpreted and printed information included either a hard-copy text or captions that were prepared ahead of time (Gates, 1971;Norwood, 1976;Stinson, Meath-Lang, & MacLeod, 1982). These studies found greater retention of the printed information.…”
Section: Comparisons Of Types Of Supportmentioning
confidence: 99%
“…Though In India at present most deaf (approximate 60-78%) do not have access to Computers, Laptops, Tabs, etc, there is very limited Deaf channels, Deaf programs, and Deaf oriented entertainment [19]. Deaf experience lack of access to technology due to hearing impairment.…”
Section: Introductionmentioning
confidence: 99%